THE INFLUENCE OF UNDERWRITER REPUTATION, AUDITOR REPUTATION, COMPANY SIZE AND COMPANY AGE ON UNDERPRICING IPO FOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2008-2013 - Ririn Salfida; Kencana Dewi; Mukhtaruddin Mukhtaruddin (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
This study aims to analyze the influence of non-accounting factors of the underpricing IPO stock in Indonesia Stock Exchange. In this study, the independent variables used are underwriter reputation, auditor reputation, company size and company age, while the dependent variable in this study is the initial return.The data used in this study are secondary data from the Indonesia Stock Exchange and the Indonesian Capital Market Directory (ICMD) from 2008 to 2013. Samples were selected using purposive sampling method. From 135 companies that conduct an IPO in 2008-2013, there are 85 companies that meet predetermined criteria. The method of data analysis used in this study is multiple linear regression. The analysis showed that company size and company age significantly influences the underpricing of IPO with negative direction. While the underwriter's reputation and the reputation of the auditor no significant effect on IPO underpricing. Limitations in this research that the criteria used to measure underwriter reputation and the reputation of the auditor only use the data tabulation of the total listed companies and the data sample in 2013 is stilldifficult to obtain because it has not published by the Indonesia Stock Exchange.